ANALISIS HAMBATAN KOMUNIKASI ANTARA ORANG TUA YANG BEKERJA DALAM MENGAWASI PERGAULAN REMAJA AKIBAT MUNCULNYA MEDIA SOSIAL - Rina Astriani; Rani Puspita (Jurnal Sosial Humaniora dan Pendidikan, 2024)
This research explores the communication barriers between working parents in monitoring adolescent social interactions through social media. The study adopts a constructivist paradigm and a qualitative phenomenological approach. Symbolic Interactionism theory is employed to understand the impact of social media on the formation of adolescents' self-concept, while Family Communication Theory highlights communication gaps between parents and children. The research findings indicate that social media can be an additional communication barrier for working parents due to adolescents' addiction to social media and the parents' limited understanding of social media usage after a lack of face-to-face interaction. Working parents need help spending quality time together and supervising their children in a hostile social media environment.